Understanding English School’s Contributions to the International Relations - Zhenhao Ma; Jie Wu (Chinese Journal of International Review)
As an integral part of International Relations (IR) theories, English School reflects the thinking of international affairs from Britain and other non-American countries in the West. The emergence of English School is the result of the split of IR academia after World War II and the extensive debate related with the behaviorist revolution in 1950–1960s. On the one hand, English School adopts a holistic method and then elaborates the notion “international society” as its label. On the other hand, compared with constructivism, English School is quite different in terms of adoption of the historical approach.